Modelling the fracture-healing process as a moving-interface problem using an interface-capturing approach. Issue 8 (11th June 2018) - Pietsch, M.; Niemeyer, F.; Simon, U.; Ignatius, A.; Urban, K.
Abstract: We present a novel numerical model of the fracture-healing process using interface-capturing techniques, a well-known approach from fields like fluid dynamics, to describe tissue growth. One advantage of this method is its direct connection to experimentally observable parameters, including tissue-growth velocities. In our model, osteogenesis, chondrogenesis and revascularisation are triggered by mechanical stimuli via mechano-transduction based on previously established hypothesis of Claes and Heigele. After experimentally verifying the convergence of the numerical method, we compare the predictions of our model with those of the already established Ulm bone-healing model, which serves as a benchmark, and corroborate our results with existing animal experiments. We demonstrate that the new model can predict the history of the interfragmentary movement and forecast a tissue evolution that appears similar to the experimental results. Furthermore, we compare the relative tissue concentration in the healing domain with outcomes of animal experiments. Finally, we discuss the possible application of the model to new fields, where numerical simulations could also prove beneficial.